Emerging Roles of Nucleoside Transporters - Pastor-Anglada, Marçal; Pérez-Torras, Sandra (Frontiers in Pharmacology, 2018)
Since human Nucleoside Transporters (hNTs) were identified by their activity as transport systems, extensive work has been done to fully characterize them at the molecular and physiological level. Many efforts have been addressed to the identification of their selectivity for natural substrates and nucleoside analogues used to treat several diseases. hNTs belong to two different gene families, SLC28 and SLC29, encoding human Concentrative Nucleoside Transporters (hCNTs) and human Equilibrative Nucleoside Transporters (hENTs), respectively. hCNTs and hENTs are integral membrane proteins, albeit structurally unrelated. Both families share common features as substrate selectivity and often tissue localization. This apparent biological redundancy may anticipate some different roles for hCNTs and hENTs in cell physiology. Thus, hENTs may have a major role in maintaining nucleoside homeostasis, whereas hCNTs could contribute to nucleoside sensing and signal transduction. In this sense, the ascription of hCNT1 to a transceptor reinforces this hypothesis. Moreover, some evidences could suggest a putative role of hCNT2 and hCNT3 as transceptors. The interacting proteins identified for hCNT2 suggest a link to energy metabolism. Moreover, the ability of hCNT2 and hCNT3 to transport adenosine links both proteins to purinergic signaling. On the other hand, the broad selectivity transporters hENTs have a crucial role in salvage pathways and purinergic signaling by means of nucleoside pools regulation. In particular, the two new hENT2 isoforms recently described together with hENT2 seem to be key elements controlling nucleoside and nucleotide pools for DNA synthesis. This review focuses on all these NTs functions beyond their mere translocation ability.